Features of microelement composition of mountain alluvial soils of the Western Caucasus - T. V. Degtyareva; A. A. Likhovid (Наука. Инновации. Технологии, 2024)
The object of the study is the microelement composition of mountain alluvial soils, the formation of which occurs quite intensively due to the activity of processes that determine the development of soil cover in mountainous relief conditions. The study is based on the analysis of features forming the system of soil compounds of microelements in alluvial soils of river valleys of the Western Caucasus using the example of the Bolshoy Zelenchuk River valley. The study specified that alluvial soils are characterized by a constant supply of microelements in the composition of suspensions and dissolved substances in river waters, which during flood spills flood the flood-plain part of river valleys. In addition, microelements are supplied mechanically from the mountain slopes directly adjacent to the river valley. A certain role is played by the processes of aerial transfer of dust particles with air flows, including those of a transboundary nature. Rising groundwater also causes the movement of dissolved forms of trace elements in mountain alluvial soils in both radial and lateral directions. Based on the results of the study, we can conclude that mountain alluvial soils are characterized by a strong connection with soil-forming rocks, which are the most important source of microelements. Features of the development of the system of soil compounds of microelements in mountain alluvial soils are determined by the specific conditions for the occurrence of soil-forming processes in them. Their study is necessary due to the important environment-forming significance of mountain alluvial soils in modern landscapes of river valleys, which are the most developed areas of mountainous countries.